Photodynamic therapy for squamous cell oral and lower lip carcinoma - V. V. Poljkin; I. S. Spichenkova; М. А. Kaplan; V. S. Medvedev; V. N. Kapinus; Е. V. Yaroslavtseva-Isaeva; А. М. Shubina; Е. V. Goranskaya; D. Yu. Syomin; М. U. Radjapova (Biomedical Photonics)
Treatment outcomes in 82 patients with primary and recurrent oral and lower lip cancer after photodynamic therapy with photosensitizer Photolon alone or combined with other methods of cancer treatment are represented. According to type and extent of the tumor the single dose of Photolon for intravenous administration accounted for 0.8–2.5 mg/kg, light dose – 100–400 J/cm2 (with wave length of 661 nm). 57 patients had PDT alone; 5 patients – in combination with distant radotherapy; 11 – with distant radiotherapy and polychemotherapy; 9 – with 252Cf interstitial therapy and polychemotherapy. For these patients 3-year overall survival rates were 85.1±4.8%, 3-year reccurence-free survival – 72.2±4.7%. The PDT for recurrent tumors, in cases when other methods were exhausted or impossible, allowed complete tumor response in 82.9% of patients, in 72.9% of them – 3-year disease free survivance. For PDT combined with distant radiotherapy (including concurrent polychemotherapy) the complete response was observed in 100% of patients with primary tumor and in 66.7% of patients with recurrent tumor. For PDT combined with interstitial neutron therapy all patients had complete tumor response. The study showed that this combination allowed decreasing the total radiation dose and radiation dose on adjacent normal tissue, thus, decreasing radiation injury.